Strategic Management of Islamic School Principals in Enhancing Leadership Effectiveness - Hilma Nur Latipah; Fiqra Muhamad Nazib; Iman Saifullah (Journal of Educational Management Research, 2026)
This study aims to analyze the management concept of madrasah principals in improving leadership quality within Islamic educational institutions. The research employed a Systematic Literature Review (SLR) method by examining relevant national and international journal articles published over the last ten years. The selected literature was identified, screened, analyzed, and synthesized systematically based on publication quality, relevance, and research focus. The findings reveal that effective madrasah principal management, encompassing planning, organizing, implementation, and supervision, significantly strengthens leadership quality, enhances teacher professionalism, promotes a positive organizational culture, and improves the overall quality of Islamic education. In addition, leadership supervision grounded in Islamic values, including amanah (trustworthiness), justice, and deliberation, supports sustainable and value-based leadership practices. The integration of managerial functions with Islamic leadership principles provides a comprehensive conceptual framework for strengthening leadership effectiveness in madrasahs. The study implies that adopting an integrated managerial and Islamic leadership approach can serve as a practical reference for madrasah principals while contributing to the theoretical development of Islamic educational management.